2020
DOI: 10.1620/tjem.250.191
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during Pregnancy Is a Predictor of Poor Perinatal Outcomes in Maternal Anorexia Nervosa: A Case Series and Single-Center Cross-Sectional Study in Japan

Abstract: Eating disorders are common psychiatric disorders among women of reproductive age, and the prevalence of eating disorders has been increasing over time in Japan and other countries. The aim of the present study was to assess perinatal outcomes in maternal anorexia nervosa in Japan and to explore methods to improve perinatal outcomes. This study consists of a case series describing 13 single pregnancies of 11 women with a history of anorexia nervosa, and a cross-sectional study comparing 13 cases with 240 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Based on the level of evidence, anaemia [ 23 25 ], caesarean section [ 7 , 26 , 27 ] and concurrent recreational substance use [ 28 , 29 ] were the most commonly reported by the studies included. In comparison to women without a history of AN, the odds ratios (OR) were 2.1 (95%CI 1.3–3.2) [ 23 ] and 2.39 (95%CI 1.20–4.76) [ 24 ] for anaemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the level of evidence, anaemia [ 23 25 ], caesarean section [ 7 , 26 , 27 ] and concurrent recreational substance use [ 28 , 29 ] were the most commonly reported by the studies included. In comparison to women without a history of AN, the odds ratios (OR) were 2.1 (95%CI 1.3–3.2) [ 23 ] and 2.39 (95%CI 1.20–4.76) [ 24 ] for anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Two case reports and two case series found that the behaviour symptoms (such as purging behaviour, restrictive eating and the use of laxatives) related to disordered eating in the woman with AN were worsened during pregnancy [ 29 32 ]. One case report found the opposite, where the patient had reduction of behaviour symptoms during pregnancy, but emotional and cognitive symptoms persisted [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Os estudos. Os estudos sugerem fortemente que as mulheres em idade reprodutiva devem ser incentivadas a não fumar ou parar de fumar, haja vista que este é um dos fatores que aumentam o risco de infertilidade (Kasahara, Ono, Higuchi, Katsura, & Hayashi, 2020;Passos, Cunha-filho & Freitas, 2004). Deve ser considerado que alguns dos motivos que levam as mulheres a parar de fumar são diferentes dos motivos dos homens.…”
Section: Discussionunclassified
“…LBW and SGA were more severe in women hospitalized for AN during pregnancy or within 2 years of delivery than in the general population. 29 In a retrospective study, Kasahara et al 28 compared the outcomes of 13 women with AN and 240 healthy controls. The authors found that AN history was associated with an increased risk of premature birth and symmetric growth restriction.…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…The study includes a small sample, and the authors report information bias due to the lack of standardization in ED diagnosis records. 28 Eagles et al 30 performed a retrospective study with records from a North East Scotland psychiatric clinic belonging to Women with AN who gave birth at the Aberdeen Maternity and Neonatal Databank (AMND). The authors compared these data with those of healthy women matched by age, year of delivery of the first baby, and parity.…”
Section: Anorexia Nervosamentioning
confidence: 99%